Training for Tennis: From Torso to Movement - Bugg, B. S. (NSCAs Performance Training Journal, 2002)
Andre Agassi or Andy Roddick hitting a running forehand for the win is a spectacular shot that all of us love to watch and may enjoy hitting ourselves! One of the keys to a powerful volley is a well-trained torso. While the torso`s involvement is ever-present in all tennis movements, the most difficult demand may very well be the rotational aspect. Rotation occurs when hitting groundstrokes, serves, and volleys. By rotating, the body is able to transfer its center of gravity into the shot, which is a major source of power. When hitting that running forehand, the torso must also have the ability to stave off injury. While proper hydration and flexibility are required for optimal power production and injury prevention, performing the necessary movement patterns is of great importance as well. In sport, the torso has four responsibilities: 1. Flexion = straight line, vertical movement with the torso 2. Rotation = circular/crossover movement with the torso 3. Stabilization = holding, without movement, with the torso 4. Lateral Flexion = side to side movement with the torso A balanced approach of all of these movements develops the torso`s ability to provide power and prevent injury. Thus, a strong torso provides off balance coordination for shot making capabilities. Though torso training may not be the most thrilling part of a training session, it is one of the most important manners in which to train for tennis. Incorporating torso training at the beginning of a training session allows players to overcome a difficult aspect of training while concurrently allowing the body to internally warm itself.